INVESTIGATION ROLE OF VITAMIN D3 AND IMMUNOLOGICAL MARKERS IN PATHOGENESIS OF HASHIMOTO THYROIDITIS - Gisson Hamed Lateef (Scholar Express Journals, 2023)
Background; The primary reason of hypothyroidism is Hashimoto's thyroiditis (HT), the most common autoimmune illness that causes thyroid cell damage due to lymphocyte invasion. Its distinctive features include an elevated amount of autoantibodies targeting thyroid peroxidase and thyroglobulin. Objective IL-38, IL-15, vitamin D3, anti-TPO, and anti-TGA characteristics are being studied with the aim of determining their role in the etiology of Hashimoto's thyroid disorders (HT).
Keywords: vitamin; IL-38; IL-15; Hashimoto thyroiditis